(untitled) (Novateur Publications, 2023)
Gratitude test the presence of Allah swt. because on His permission so that book entitled The Existence of Local Wisdom in North Sulawesi via Storytelling Batik can writer finish. The book we made This is results research that examines special cloth typical of North Sulawesi with choose Wrong except, namely batik tells a story. Book This made For tell to para reader about cloth typical North Sulawesi region, in particular cloth famous specialty with the name Batik Tells Stories . Batik tells a story lots create cloth with various motifs. Of course only the motif that is raised yes friend about depicting culture characteristic typical North Sulawesi area. The motifs outlined in cloth the of course just loaded with meaning. With thereby the presence of storytelling batik this very influence development culture in North Sulawesi in particular cloth typically. In make writing this of course just Lots involve participating parties support presence book this. Writer visit direct to storytelling batik shop and chat direct with owner at a time creator of batik telling stories. By Because the, we the writer deliver accept thank you to all the party who did it help so that writing this can finished. Accept thank you not until writer convey to mother cool matinda as creator at a time the owner of batik tells the story donate the time for tell and give information in a way detailed about Batik Telling Stories.